(untitled) (Global Journal of Management and Business Research, 2025)
The article examines the analysis of the conditions under which the economic activity of a leasing company, as a necessary link in the current crisis between manufacturers of modern equipment and enterprises operating on the market using it, is cost-effective. Since the lessor can simultaneously act both as a lessee or buyer of equipment from the manufacturer, on the one hand, and as a lessor of this equipment for the user enterprise, on the other hand, the analysis of the effectiveness of its activities was carried out in the form of an assessment of the effectiveness of financial inflows and outflows of the lessee and the lessor. An economic and mathematical analysis of the reduced net income of the lessor was carried out for four options for such a project: two options when the lessor acts as a tenant and a lessor, as well as a buyer and a lessor when using equity capital, and two similar options when using a loan. Analytical indicators of project effectiveness -reduced net income and profitability index -are supplemented by the payback period indicator, for the calculation of which, in practice, a laborious recursive-logical procedure is used. To obtain an analytical expression for the payback period, an original technique was used based on the replacement of a discrete stream of payments with a financially equivalent continuous stream.